The Role of Saudi Women in Leading Institutions and its Impact on the Performance of all Organizations - Alyamani, Khaled A. Z.; Morsi, Sami A. (Journal of Posthumanism, 2025)
This study looks at the changing women’s contribution to formal leadership roles in Saudi Arabia and assesses how their greater presence affects cross-sector organizational performance. By synthesizing available literature, analyzing the latest statistics, and reviewing pertinent case studies, this paper highlights the status of women in leadership positions within Saudi organizations, as well as the performance indicators associated with these organizations. The results indicate that organizations with greater proportions of women in leadership tend to show better results in terms of innovation, financial performance, employee engagement, and organizational culture. This advocacy research adds to the growing literature on women and gender issues, particularly concerning leadership in Saudi Arabia, offering contextual relevance to policymakers and organizational leaders focused on performance improvement through women’s inclusive leadership strategies.